Paclitaxel-induced Hypersensitivity Reaction - Cyril Sajan; Elizabeth Jacob; Varunsingh Saggu; Rajesh Hadia; Hemraj Singh Rajput (Journal of the Scientific Society)
An immunological response that results in an adverse reaction due to a certain drug is known as a hypersensitivity reaction (HSR). Such type of reactions is seen with antineoplastic agents. HSR is commonly seen with one of the chemotherapeutic agents, namely, paclitaxel. Occurrence of such reactions can be suppressed with the administration of premedications (dexamethasone 20 mg intravenous [IV], diphenhydramine 50 mg IV, and famotidine 20 mg IV). Mainly, the paclitaxel consists of paclitaxel IP, polyoxyl 35, castor oil IP (Cremophor ELP), and dehydrated alcohol IP. The mechanism of this reaction is not known exactly, but it is believed that the reaction may be occurring due to paclitaxel itself or its vehicle castor oil IP (Cremophor ELP). Molecules present in Cremophor ELP are found to be similar in structure to certain nonionic block copolymers that activate complement proteins (the proteins involved in various immune processes).